4k-3(k-8)=2(3-5k)+7

Simple and best practice solution for 4k-3(k-8)=2(3-5k)+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4k-3(k-8)=2(3-5k)+7 equation:


Simplifying
4k + -3(k + -8) = 2(3 + -5k) + 7

Reorder the terms:
4k + -3(-8 + k) = 2(3 + -5k) + 7
4k + (-8 * -3 + k * -3) = 2(3 + -5k) + 7
4k + (24 + -3k) = 2(3 + -5k) + 7

Reorder the terms:
24 + 4k + -3k = 2(3 + -5k) + 7

Combine like terms: 4k + -3k = 1k
24 + 1k = 2(3 + -5k) + 7
24 + 1k = (3 * 2 + -5k * 2) + 7
24 + 1k = (6 + -10k) + 7

Reorder the terms:
24 + 1k = 6 + 7 + -10k

Combine like terms: 6 + 7 = 13
24 + 1k = 13 + -10k

Solving
24 + 1k = 13 + -10k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '10k' to each side of the equation.
24 + 1k + 10k = 13 + -10k + 10k

Combine like terms: 1k + 10k = 11k
24 + 11k = 13 + -10k + 10k

Combine like terms: -10k + 10k = 0
24 + 11k = 13 + 0
24 + 11k = 13

Add '-24' to each side of the equation.
24 + -24 + 11k = 13 + -24

Combine like terms: 24 + -24 = 0
0 + 11k = 13 + -24
11k = 13 + -24

Combine like terms: 13 + -24 = -11
11k = -11

Divide each side by '11'.
k = -1

Simplifying
k = -1

See similar equations:

| 50-5x=80-17x | | 15y-(3-[4y+4]+57)=2-y | | 2(6-4x)=21-9x | | -7+(8z+2)=(7z+5)+1 | | 3.7+15.09= | | -1/3m=-8 | | r^2-8=26 | | Z-2=4+9x | | 4.5[h-6]= | | 19x+3=11x-2 | | 5/8j-3/4=1/2 | | .5d-3/4=3/5d | | 79-2x=88-3x | | 3y-7=4y+8 | | -1/2(6x-1/3) | | 5p^2=230 | | 9x-8=x+10 | | 5x^2+4x-48=0 | | -2=-3/5x-3 | | 5(x)=20*1.03x | | -6b+2b-5b-3b+4b=-8b | | 40n^2+36n-28=0 | | 3x+20=2x+20-2r-40 | | 24+7=-4-9 | | -6b+2b-5b-3b+4b=18b | | y-5=0.11(x+9) | | 3n+7=82 | | 16=10-(4x+2) | | 5.34086e=231 | | -16t^2+80t+4=h(t) | | 4x=12+3x-x | | 1/2(6x-1/3) |

Equations solver categories